The importance of vocabulary in teaching the language of law and ways of its assimilation - Zhanzhigitov, S.Zh. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article defines the essence and structure of the professional terminological competence of future lawyers based on the study of such fundamental concepts as “linguistic competence” and “professional competence”; also identifies the main factors determining the essence of the professional terminological competence of future lawyers. The purpose and objective of the article is to consider the study of legal terms from the point of view of Kazakh linguistics, to determine the scientific and methodological foundations for the development of legal (professional) terminological competence of future lawyers, to discuss alternative translation issues. During the writing of the article, we have considered information, pragmatic, cognitive activities in the structure of law. This is the main scientific novelty of the article. The following research methods were used in this work: observation method, description method, systematization method, methods of linguostatistical and structural analysis. The research work has theoretical and practical significance, since the presented concept is valuable information for students of the legal field. It is necessary to emphasize once again that in order to fully master the profession, it is necessary to know and correctly use lexical units called special concepts that are terms. They make up the semantic core of a language for specific purposes. Legal terms have a number of unique characteristics that allow them to be divided into a special category. These characteristics include the abstractness of legal concepts; the ability of judicial and legal organizations to introduce new meanings of terms; the importance of judicial interpretation for the formation of the meaning of a legal terminological unit. Each term itself is connected in a certain way and takes its place among other elements of the system of terms that exist in certain relationships. A systematic approach to the study of industry terminology will undoubtedly optimize the learning process. This, in turn, reflects the consistency of scientific knowledge.
Құқық тілін оқытуда лексиканың маңызы және оның меңгерту жолдары
Значимость лексики в обучении языку права и пути ее усвоения
Keywords: competence; linguistic competence; legal term; judicial interpretation; terminological system; structural models; legal vocabulary; definition